A diplodocid sauropod dinosaur from the Late Jurassic Cañadón Calcáreo Formation of Chubut, Argentina - Rauhut, Oliver Walter Mischa (2015)
Late Jurassic dinosaur faunas from the Southern Hemisphere are still poorly known, and it thus remains unclear whether or not the famous Tendaguru fauna (Kimmeridgian–Tithonian, Tanzania) represents a typical Gondwanan dinosaur assemblage of that time. In South America, only the Oxfordian–Kimmeridgian Cañadón Calcáreo Formation of Chubut Province, Argentina, has yielded more than isolated Late Jurassic dinosaur remains so far. Here we report fragmentary remains of a dipolodocid sauropod from this unit, representing the first record of this family from the Late Jurassic of South America. Incorporating the basal macronarian Tehuelchesaurus, an unidentified brachiosaurid, the dicraeosaurid Brachytrachelopan, and the diplodocid described here, the taxonomic composition of the sauropod fauna from the Cañadón Calcáreo Formation is remarkably similar to that of the Tendaguru Formation, but also to roughly contemporaneous faunas in North America and Europe. The diverse non-neosauropodan sauropod fauna known from the early Middle Jurassic (Aalenian–Bajocian) of the same depositional basin within Chubut Province is congruent with the dominance of non-neosauropodan sauropods in continental faunas globally to at least the Bathonian. These assemblages suggest a rapid faunal turnover within sauropod faunas in the late Middle Jurassic-earliest Late Jurassic at least in western Pangea, through which basal eusauropods were replaced by diplodocoid and macronarian neosauropods. Taking paleogeographical reconstructions into account, this faunal replacement might have taken place in a surprisingly short time interval of maximally five million years close to the end of the Middle Jurassic.